Peningkatan Kapasitas Guru SMK Pertanian melalui Pemanfaatan AI dalam Modul Pembelajaran Berbasis Proyek - Lubis, Mitra Musika; Effendi, Ihsan; Kuswardani, Retna Astusi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This community service activity organized by Universitas Medan Area aims to enhance the capacity of vocational agriculture teachers in developing project-based learning (PjBL) modules integrated with artificial intelligence (AI) technology. The training was conducted over two days at SMK Negeri SPP Asahan and involved teachers from various agricultural expertise areas. Participants were equipped with knowledge and skills to utilize digital platforms such as ChatGPT, Canva AI, and Teachable Machine to design innovative, contextual, and student-centered learning modules tailored to the needs of vocational school students. The results of the activity show that the training effectively improved teachers’ digital literacy, encouraged creativity, and strengthened their preparedness to face learning challenges in the digital era.